Green Technology of Processing Chicken Egg Shell Waste into Nanocalcium for Osteoporosis Prevention: A Literature Study - Sunardi (Jurnal Serambi Engineering, 2024)
Egg shells have a high enough calcium content which can.be used as a source of calcium. The elderly population is increasing globally and is predicted to reach 1.5 billion by 2050. The quality of life of the elderly must be considered, for example by developing functional foods for the elderly. This literature review will discuss the development of functional foods to reduce the risk of osteoporosis in the elderly. Oxidative stress is one of the factors that accelerates the occurrence of osteoporosis. Various antioxidants, including vitamin C, vitamin E, polyphenols, or lycopene, have been shown to have antioxidant activity, thereby reducing the risk of osteoporosis. In addition, the application of nanocalcium from chicken egg shells in various food products has been reported to increase calcium intake, and its use is environmentally friendly because it can contribute to reducing food waste. The application of antioxidants and nanocalcium can be a good combination, but the amount of some antioxidants must be considered so as not to interfere with calcium bioavailability. Therefore, this literature review aims to explore functional foods for the elderly to reduce the risk of osteoporosis, especially with antioxidants and nanocalcium from chicken egg shells. Eating preferences and eating patterns of the elderly are also a consideration to determine the appropriate form of functional food for the elderly. The results presented in this literature review can be the basis for the development of new food products enriched with nanocalcium from chicken egg shells for the elderly.